Implementation Of Physical Education In Elementary School A Entire Musi Rawas District With Online Learning System In The Middle Of The Covid-19 Pandemic - Tono Sugihartono; Santun Sihombing; Bayu Nirwana Sandi (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2021)
This study aims to determine the Implementation of Physical Education in Elementary Schools in- Musi Rawas Regency with the Online Learning System in the Middle of the Covid-19 Pandemic. This type of research is a qualitative descriptive study. Instruments and data collection techniques using observation, interviews, questionnaires, and documentation. The subjects in this study were 30 PJOK teachers. The object of this research is the implementation of elementary school physical education in-Musi Rawas Regency. Based on all the research results that have been conducted by researchers, the results obtained according to the results of observations have a moderate category with a percentage (57.87%), the results of the interview are in a good category with a percentage (65% ), and the results of the questionnaire have a good category with a percentage ( 77.36%). So the researchers have determined that the results of the 3 research guidelines above have a good category with a percentage (66.74%), so it can be concluded that the implementation of physical education in elementary schools throughout the Musi Rawas district with an online learning system in the midst of the Covid-19 pandemic is included in the Good category.